대기 전력 저감을 위한 LLC 공진 컨버터의 출력 전압 제어 - 이학철 (The Graduate School, Ajou University, 2024)
This paper proposes a method of controlling the output voltage of an LLC resonant converter to reduce standby power. The LLC resonant converter in the normal mode state maximizes the voltage gain through the design of a frequency domain lower than the resonant frequency. When entering the standby mode, the power circuit of the LED TV cuts off the output load of the backlight unit board, etc., and outputs minimal power. A circuit to lower the output voltage is added to the feedback circuit of the output terminal. On the primary side, a burst operation is performed to receive a lowered output voltage and stop switching for a certain period by the feedback stop voltage. Accordingly, the primary current decreases. Standby power consumed is reduced due to the decrease in the primary current. The efficiency improvement of the proposed standby power is verified through an experiment.|본 논문에서는 대기 전력의 저감을 위하여 LLC 공진형 컨버터의 출력 전압을 제어하는 방법을 제안한다. 정상 모드 상태에서의 LLC 공진형 컨버터는 공진 주 파수보다 낮은 주파수 영역의 설계를 통하여 전압 이득이 최대화된다. 대기 모드 상태로 진입하면 LED TV의 전원 회로는 백라이트유닛 보드 등의 출력 부하를 차 단하고 최소한의 전력을 출력한다. 출력단의 피드백 회로에 출력 전압을 낮추는 회로를 추가한다. 1차측에서는 낮아진 출력 전압을 받고 피드백 정지 전압에 의하 여 일정 구간 동안 스위칭을 멈추는 버스트 동작을 수행한다. 이에 따라 1차측 전 류는 감소한다. 1차측 전류의 감소로 인하여 소비되는 대기 전력이 감소한다. 제안 한 대기 전력의 효율 개선을 실험으로 검증한다.
학위논문(석사)--IT융합공학과,2024. 8
Keywords: LLC; 대기 전력